Information Communication Technology, Identity, and Brunei Society: A Critical Literature Review - Besar, Norainna (SUSURGALUR, 2015)
ABSTRACT: Modernity reduces the overall riskiness of certain areas and modes of life, yet at the same time introduces new risk parameters largely or completely unknown to previous eras. Spread of new communication technologies, and above all the internet as well as communication networks, has dramatically influenced identities of individuals and their cultures. A study of new ICT (Information and Communication Technology), particularly as the internet, is changing the way the world works and will continue to do so into the future. By its unprecedented power to move and process information, it is impacting on global living patterns, culture, and governance; in fact, the internet impacts on every aspect of our society today. The question is whether a country like Brunei Darussalam can endure preserving its values, while the internet keeps exerting a damaging influence that can threaten its identity? Thus, this critical review will focus on the internet as a new form of ICT and look at the social impact of its potential threat to the identity of Brunei Darussalam society.KEY WORD: Information and Communication Technology; Identity and Culture; Brunei Society; Internet; Social Impacts.Â IKHTISAR: âTeknologi Komunikasi Maklumat, Identiti, dan Masyarakat Brunei: Satu Kajian Literatur Kritikalâ. Kemodenan mengurangkan sifat berbahaya keseluruhan kawasan-kawasan tertentu dan mod kehidupan, namun pada masa yang sama memperkenalkan parameter risiko baru sebahagian besarnya atau benar-benar tidak diketahui pada era sebelumnya. Penyebaran teknologi-teknologi komunikasi baru, dan di atas semua itu internet serta rangkaian komunikasinya, telah mempengaruhi secara mendadak identiti individu dan budaya mereka. Kajian teknologi maklumat dan komunikasi baru, terutamanya internet, telah mengubah cara bekerja dan akan terus membuat pelbagai perubahan di masa hadapan. Kuasa yang ada pada internet dalam menghantar dan memproses maklumat, memberi kesan kepada corak hidup global, budaya, dan pentadbiran; bahkan pada setiap aspek kehidupan masyarakat pada hari ini. Persoalannya ialah adakah sesebuah negara seperti Brunei Darussalam boleh bertahan dalam memelihara nilai-nilai murni, sedangkan internet mempunyai pengaruh yang merosakkan dan boleh mengancam identiti sebuah negara? Oleh itu, kajian ini penting dengan memberi fokus kepada internet sebagai salah satu bentuk teknologi maklumat dan komunikasi yang baru, dan juga melihat ancamannya yang berpotensi untuk memberi kesan kepada masalah sosial dan identiti masyarakat Brunei Darussalam.KATA KUNCI: Teknologi Maklumat dan Komunikasi; Identiti dan Budaya; Masyarakat Brunei; Internet; Kesan Sosial.About the Author: Norainna Besar is a Lecturer at the Academy of Brunei Studies UBD (University of Brunei Darussalam), Jalan Tunku Link, BE 1410, Bandar Seri Begawan, Negara Brunei Darussalam. For academic interests, the author is able to be contacted via e-mail at: norainna.besar@ubd.edu.bnHow to cite this article? Besar, Norainna. (2015). âInformation Communication Technology, Identity, and Brunei Society: A Critical Literature Reviewâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.3(2), September, pp.247-256. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Chronicle of the article: Accepted (August 13, 2015); Revised (September 15, 2015); and Published (September 30, 2015).